2019
DOI: 10.3390/app9020326
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Characterization of Cell Growth on Reduced Graphene Oxide–Gold Nanoparticles Electrodeposited on Indium Tin Oxide Electrodes

Abstract: The improved binding ability of graphene–nanoparticle composites to proteins or molecules can be utilized to develop new cell-based assays. In this study, we fabricated reduced graphene oxide–gold nanoparticles (rGO-AuNP) electrodeposited onto a transparent indium tin oxide (ITO) electrode and investigated the feasibility of the electrochemical impedance monitoring of cell growth. The electrodeposition of rGO–AuNP on the ITO was optically and electrochemically characterized in comparison to bare, rGO-, and AuN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…S.R. Chinnadayyala and coworkers in their article: Electrochemical Impedance Characterization of Cell Growth on Reduced Graphene Oxide-Gold Nanoparticles Electrodeposited on Indium Tin Oxide Electrodes [7], describe the fabrication of reduced graphene oxide-gold nanoparticles (rGO-AuNP) electrodeposited onto a transparent indium tin oxide (ITO) electrode and investigate the feasibility of monitoring HEK293 cell growth by electrochemical impedance, in combination with the microscopic observation of the cells transfected with a green fluorescent protein expression vector. Results demonstrate the high potentiality of the rGO-AuNP/ITO electrode for label-free and real-time impedimetric cell-based assays, since the rGO-AuNP hybrids are biocompatible and induce an increase in cell adherence to the electrode when compared to the bare, AuNP-, or rGO-deposited ITO electrode.…”
Section: Optical and Electrochemical Sensing For Eukaryotic Cells Andmentioning
confidence: 99%
“…S.R. Chinnadayyala and coworkers in their article: Electrochemical Impedance Characterization of Cell Growth on Reduced Graphene Oxide-Gold Nanoparticles Electrodeposited on Indium Tin Oxide Electrodes [7], describe the fabrication of reduced graphene oxide-gold nanoparticles (rGO-AuNP) electrodeposited onto a transparent indium tin oxide (ITO) electrode and investigate the feasibility of monitoring HEK293 cell growth by electrochemical impedance, in combination with the microscopic observation of the cells transfected with a green fluorescent protein expression vector. Results demonstrate the high potentiality of the rGO-AuNP/ITO electrode for label-free and real-time impedimetric cell-based assays, since the rGO-AuNP hybrids are biocompatible and induce an increase in cell adherence to the electrode when compared to the bare, AuNP-, or rGO-deposited ITO electrode.…”
Section: Optical and Electrochemical Sensing For Eukaryotic Cells Andmentioning
confidence: 99%
“…PLL functions as an attachment factor that enhances cell adhesion due to its strong affinity to proteins and electrostatic interactions between the positive charges on the PLL molecule and the negative charges on the cell membrane [ 17 ]. Thus, PLL is commonly used to enhance cell adhesion, spreading, proliferation and differentiation [ 18 , 19 , 20 ]. It has been shown that poly(ethylene terephthalate) stent surface modification with PLL promotes endothelial cell adhesion and growth [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%